A Computational Approach Identified Andrographolide as a Potential Drug for Suppressing COVID-19-Induced Cytokine Storm - Rehan, Mohd; Ahmed, Firoz; Howladar, Saad M.; Refai, Mohammed Y.; Baeissa, Hanadi M.; Zughaibi, Torki A.; Kedwa, Khalid Mohammed; Jamal, Mohammad Sarwar (Frontiers in Immunology, 2021)
Background: The newly identified betacoronavirus SARS-CoV-2 is the causative pathogen of the coronavirus disease of 2019 (COVID-19) that killed more than 3.5 million people till now. The cytokine storm induced in severe COVID-19 patients causes hyper-inflammation is the primary reason for respiratory and multi-organ failure and fatality. This work uses a rational computational strategy to identify the existing drug molecules to target host pathways to reduce the cytokine storm. Results: We used a “host response signature network” consist of 36 genes induced by SARS-CoV-2 infection and associated with cytokine storm. In order to attenuate the cytokine storm, potential drug molecules were searched against “host response signature network”. Our study identified that drug molecule andrographolide, extracted from medicinal plant Andrographis paniculate, has the potential to bind with crucial proteins to block the TNF-induced NFkB1 signaling pathway responsible for cytokine storm in COVID-19 patients. The molecular docking method showed the binding of andrographolide with TNF and covalent binding with NFkB1 proteins of the TNF signaling pathway. Conclusion: We used a rational computational approach to re-propose existing drugs targeting host immunomodulating pathways. Our study suggests that andrographolide could bind with TNF and NFkB1 proteins, block TNF-induced cytokine storm in COVID-19 patients, and warrant further experimental validation.